Social networks and theirrole in supporting e-learning technologies The point of view of the professors of the Department of Media and Communication Sciences at the University of Msila - morzouglal, ibrahim (Journal of Social Sciences and Humanities, 2023)
The most important characteristic of the end of the twentieth century and the beginning of the twenty-first century is the emergence of information and communication technologies and the resultingdevelopments in all fields. Especiallybecause of its fast and efficient services, and everyindividualcould not do withoutit, especiallyresearchers. Researchersalwaysstrive to bepresentthroughthiselectronic and virtualspace, and the Internet is the first port that enables them to access, and with the development of websites down to the second generation web2.0, whichis a modern generationthatis more interactive and more applied and alsocontainsmany new and recentlydeveloped technologies, soresearchers must keep up withThese modern technologies and use them in their future projects and research. The web 2.0 technologyisbased on the idea of social networks, which have become the pulse of life on the Internet.It is rare thatyoufind a professorwhodoes not have a Facebook account or whodoes not use Twitter, or whodoes not have a resume on LinkedIn...etc. Thus, the life and pulse of the Internet takes place, as these services generate a network of strong and interactive interdependence for creativity each in his field, and for communication with others in a society that depends mainly on information and how to benefit from it with the least possible effort and cost, and also in the appropriate time and place. All this if if we want to keep abreast of recent developments in knowledge societies. Based on the foregoing, thisstudy came to show us the extent to whichresearchers use these social networks, as well as the most important areas in whichthey use them, and how itenabledthem to spread theirlessonsthroughthem. The study was conducted with the professors of the Department of Media and Communication Sciences at the University of M'Sila, in order to find out the actual extent to which the professors use these networks, and to explore their opinions and points of view on this subject.